Implementation of Fuzzy Logic on Adding Sodium Bicarbonate and Carboxy Methyl Cellulose (CMC) Concentrations to the Texture of Wet Noodles - Sabrina Anjani; Fiqri Nurfadillah; Ester Angeline; Nanda Octavia; Muhammad Danang Mukti Darmawan; Ilham Arrizqillah; Fajar Septiandi; Ragil Arimbi Nuryan Putri; Annisa Salsabila Suryawan; Alya Agustin; Eka Dewi Anisyah Azis; Maghfira Syafiqa; Muhammad Daffa Dzikra Martanegara; Syahla Sandrina; Alya Retno Hasyyati; Selva Rafania Haifa; Mrr. Lukie Trianawati (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
Abstract The purpose of this study was to identify appropriate concentrations of sodium bicarbonate and CMC in order to produce wet noodles with textures preferred by consumers. The steps used in this study are to conduct a literature study to obtain data in the form of input variables, namely sodium bicarbonate and Carboxy Methyl Cellulose (CMC), and output, namely texture. The input variables are fuzzified, and then the fuzzy rules and inference are determined by Mamdani and defuzzification methods. Data processing using the Mamdani method is carried out with the help of the Matlab application. The result of this study is the formulation of sample 1 with the addition of 0.6% sodium bicarbonate and 0.2% CMC and sample 2 with the addition of 0.6% sodium bicarbonate and 0% CMC, which are recommended to consumers because they produce the preferred texture of wet noodles.